Analysis of VAT-Tax- payment system of CEAT Bangladesh Limited - Khan, MD. Barkat Sadique (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.